2013
DOI: 10.5539/ep.v2n2p66
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Soil Contamination through E-Waste Recycling Activities in Tema Community One

Abstract: The study investigated the level of heavy metal concentration in soils at e-waste recycling sites at Tema Community One. Two soil samples were collected from six different sites for laboratory analysis with a seventh location serving as a control. Heavy metals in soil samples were analyzed by digestion method and the use of atomic absorption spectrophotometer. The concentrations of Cadmium, Copper and Mercury were all higher at all the sites than those obtained for the control. The site that recorded higher co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…For instance, the number of mobile users in the year 2020 stood around 7 billion; projections suggest further increase by several hundreds of million in the coming years (Statista, 2021). Although the adoption of technology requiring the use of mobile phones and computers has contributed immensely to the development of the society, poor management of e-wastes has been associated with both environmental pollution (Amfo-Otu et al, 2013; Caravanos et al, 2011; Li et al, 2011) and health-related problems (Manmohit et al, 2018; Ohajinwa et al, 2019) in developing countries where infrastructure for effective recycling of e-waste is lacking. The situation in Ghana may not be different from other developing countries where large volumes of e-waste are generated annually.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the number of mobile users in the year 2020 stood around 7 billion; projections suggest further increase by several hundreds of million in the coming years (Statista, 2021). Although the adoption of technology requiring the use of mobile phones and computers has contributed immensely to the development of the society, poor management of e-wastes has been associated with both environmental pollution (Amfo-Otu et al, 2013; Caravanos et al, 2011; Li et al, 2011) and health-related problems (Manmohit et al, 2018; Ohajinwa et al, 2019) in developing countries where infrastructure for effective recycling of e-waste is lacking. The situation in Ghana may not be different from other developing countries where large volumes of e-waste are generated annually.…”
Section: Introductionmentioning
confidence: 99%
“…The metals in the plastic components while contained within the plastic matrix do not leach and are not bioavailable (Robinson et al, 2009) but with the present practice in Nigeria of open burning to reduce waste volume (Owoso, 2016), metals in the WEEE plastics may pollute the environment through volatilization and washing of the ash resulting from burning activities along with leachates into the soil and water used for domestic purposes. Copper in the plastic can serve as catalyst for the formation of toxic dioxins and furans from brominated flame retardants in the plastic (Amfo-Otu et al, 2013). These inappropriate e-waste management practices may result in human exposure to high levels of these metals and toxins.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have pointed out that the generation of e-waste is considered one of the fastest-growing solid waste streams in the world [9][10][11]. The development of society has been triggered by the adoption of technology, which requires the use of electronic equipment such as mobile phones and computers [12,13], but due to poor management of this waste from electrical and electronic equipment (EEE) and related materials, the world is now facing associated environmental pollution [14][15][16] and health-related problems [17,18]. Studies conducted on behalf of the United Nations (UN) showed that anywhere between 20 and 50 million tons of e-waste are generated globally and the growth rate of e-waste is nearly three times the growth rate of the municipal solid waste stream [19].…”
Section: Introductionmentioning
confidence: 99%